2010
DOI: 10.1093/rheumatology/keq087
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of MPO-ANCA epitopes in SCG/Kj mice by 15-deoxyspergualin treatment restricted by IgG2b associated with crescentic glomerulonephritis

Abstract: These results strongly suggest that DSG treatment of SCG/Kj mice leads to the reduction of risk antibodies in IgG2b and normalization of B-cell clones accompanied by recovery of the cytokine and chemokine balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In particular, many kinds of MPO-ANCAs have a wide range of epitopes that exert pharmacological effects. 27,28 Alternatively, the pharmacological action of VasSF may be against an autoantibody to moesin. [29][30][31] Notably, however, the VasSF target antigen, VAP2, associates with AP1 to form high-density lipoprotein (HDL), which has anti-inflammatory action.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, many kinds of MPO-ANCAs have a wide range of epitopes that exert pharmacological effects. 27,28 Alternatively, the pharmacological action of VasSF may be against an autoantibody to moesin. [29][30][31] Notably, however, the VasSF target antigen, VAP2, associates with AP1 to form high-density lipoprotein (HDL), which has anti-inflammatory action.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that SCG/Kj mice have urinary abnormalities, crescent formation and increase in MPO–ANCA titers . Therefore, we first monitored urinary protein and hemoglobin in SCG/Kj mice from 5 to 14 weeks of age.…”
Section: Resultsmentioning
confidence: 99%
“…Because it has been reported that a spleen T cell subset expressing both CD3 and B220 in SCG/Kj and MRL/ lpr mice is caused by Fas mutation and leads to a defect in Fas‐mediated apoptosis, we further examined changes in the population of the CD3 + B220 + T cell subset with aging. FACS analysis of splenocytes showed that CD3 + B220 + T cells were rarely present in control C57BL/6 mice but their numbers were increased in SCG/Kj mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple genetic associations with MPO-ANCA development in SCG/Kj mice have been defined (141). This model has also been used to investigate possible treatments for ANCA-associated GN, including 15-deoxyspergualin (142,143) and omega-3 fatty acid eicosapentaenoic acid (EPA) (144). Dendritic cell transfer studies have implicated NETs in the development of autoimmunity to MPO and PR3 (59).…”
Section: Animalmentioning
confidence: 99%